EFFECT OF ONION JUICE (ALLIUM CEPA) ON PERFORMANCE, EGG QUALITY TRAITS, BIOCHEMICAL AND HEMATOLOGICAL PARAMETERS IN LAYING HENS - A. Iqbal1; I. Bayram (Journal of Animal and Plant Sciences, 2020)
The present study aimed to evaluate the effect of onion juice through drinking water, on the production, egg quality, hematological and immune parameters in laying hens. A total of 240 Babcock hens (40 weeks old) were divided randomly into 5 groups (48 birds in each) and each group was further subdivided into 8 replicates, containing 6 birds in each subgroup. Onion juice at the rate of 0%, 0.25%, 0.5%, 1%, and 2% was added to the drinking water offered to groups A, B, C, D, and E, respectively for 12 weeks. Egg weight, and mean water consumption was increased significantly (P≤0.05) in group C. Moreover, egg mass also increased in group E supplemented with 2% onion juice. Regarding immunity, the 2% Onion juice group produced higher IgG at 6 weeks and 12 weeks of study as compared to control and other supplemented groups in the immunological response of laying hens vaccinated against the Newcastle Disease virus. For serological parameters, at the 6th week, cholesterol, LDL, and calcium significantly (P≤0.05) increased in group E however, in the 10th-week only ALT level increased in group B over control. For hematological parameters, only the hemoglobin level was found to be higher in the 1% onion juice group. It is concluded that the addition of 0.5mg/L onion juice in the laying hens via water had meaningfully increased egg weight and water intake while supplementation of 2mg/L onion juice had ominously increased egg mass and immunity concerning an increase in IgG level in laying hens. Though, other production and performance parameters, egg quality traits, hematological parameters, and serological parameters persisted non-significant.
Keywords: Onion juice; Laying hen; Egg yield; Immunity; Blood parameters.